2016
DOI: 10.1016/j.amsu.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and properties of the biological prosthesis Permacol™ in pediatric surgery: A large single center experience

Abstract: IntroductionThe use of prosthetic patches of non-absorbable materials represents a valid tool in the treatment of abdominal wall and diaphragmatic defects in pediatric age. In recent years research has developed biological dermal scaffolds made from a sheet of acellular matrix that can provide the desired support and reduce the occurrence of complications from non-absorbable implant. We present our experience and a systematic review to evaluate the use of biologic prosthesis for abdominal wall closure in pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The use of both has been reported in patients with gastroschisis, omphalocele, congenital diaphragmatic hernia, incisional hernia, and pediatric transplant recipients with comparable results in terms of infection, seroma formation, and recurrence. [ 16 17 18 19 20 21 22 ] In the series of 24 patients reconstructed with SURGISIS ™ reported by Naji et al ., two developed recurrences, which resolved spontaneously at a 2-year follow-up. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…The use of both has been reported in patients with gastroschisis, omphalocele, congenital diaphragmatic hernia, incisional hernia, and pediatric transplant recipients with comparable results in terms of infection, seroma formation, and recurrence. [ 16 17 18 19 20 21 22 ] In the series of 24 patients reconstructed with SURGISIS ™ reported by Naji et al ., two developed recurrences, which resolved spontaneously at a 2-year follow-up. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…But this crosslinked matrix did not demonstrate significant difference compared to e-PTFE (Mitchell et al, 2008). Recently, Filisetti et al reported their own experience and a literature review on Permacol® in pediatric surgery (Filisetti et al, 2016). One can note that there are no details on the indication of Permacol® in diaphragmatic hernia apart from four records concerning, for two of them, late discoveries of the pathology and, for two others, secondary interventions after Gore-Tex failures.…”
Section: Materials Used As Diaphragmatic Prosthesismentioning
confidence: 99%